Media literacy in action : questioning the media - Hobbs, Renee (Lanham, Rowman & Littlefield, 2021)
"To thrive in a media-saturated society, people need to ask critical questions about what we watch, see, listen to, read and use. Covering topics from news and information to the internet to media consumption and addiction, this key textbook provides the tools to both empower and protect students as they navigate our increasingly complex media environment"--
What is media literacy? -- Why are media important? -- How do search engines work? -- How do people get the news? -- What is the difference between advertising, public relations, and propaganda? -- Why are we attracted to characters and stories? -- Why do people prefer different kinds of music, movies, and TV shows? -- Who decides what makes media "good"? -- How do people decide who and what to trust? -- How do media companies make money? -- Is social media free? -- Why do people worry about stereotypes? -- Is my brother addicted to media? -- How do people become media literate?
Includes bibliographical references and index.
Keywords: Media literacy